Hemangioblastoma of the cervical part of the spinal cord in the course of von Hippel-Lindau syndrome - Małecki, Krzysztof; Krzystolik, Karol; Cybulski, Cezary; Lubiński, Jan; Korzeniowski, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2006)
A 37-year-old patient was irradiated after a subtotal excision of the hemangioblastoma of the cervical spinal cord. On the basis of history, physical examination and performed additional tests, the diagnosis of VHL syndrome was established. The genetic examination revealed VHL gene mutation. Genetic tests were also performed in two children of the patient and did not reveal any mutations. The last one child was not examined. In 1998 the patient underwent coagulation because of hemangioblastoma recurrence in the right retina. In 2003 patient developed a progressive disease in the kidneys. The patient died in December 2003.